2018
DOI: 10.3389/fonc.2018.00082
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Reprogramming in Thyroid Carcinoma

Abstract: Among all the adaptations of cancer cells, their ability to change metabolism from the oxidative to the glycolytic phenotype is a hallmark called the Warburg effect. Studies on tumor metabolism show that improved glycolysis and glutaminolysis are necessary to maintain rapid cell proliferation, tumor progression, and resistance to cell death. Thyroid neoplasms are common endocrine tumors that are more prevalent in women and elderly individuals. The incidence of thyroid cancer has increased in the Past decades, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 162 publications
(292 reference statements)
4
47
0
Order By: Relevance
“…Our statistical models were based on hundreds of metabolites and lipids detected by DESI-MS in benign and malignant tissue that are predictive of disease state and biologically relevant. Many of the differentially expressed genes reported in the Afirma GEC are involved in metabolic pathways, such as glycolysis, gluconeogenesis, and the tricarboxylic acid cycle, processes which are highly relevant in cancer metabolism (30)(31)(32). In our benign versus FTC model, various metabolite intermediates involved in critical metabolic pathways were selected for FTC characterization, including malate, glutamate, and succinate.…”
Section: Discussionmentioning
confidence: 99%
“…Our statistical models were based on hundreds of metabolites and lipids detected by DESI-MS in benign and malignant tissue that are predictive of disease state and biologically relevant. Many of the differentially expressed genes reported in the Afirma GEC are involved in metabolic pathways, such as glycolysis, gluconeogenesis, and the tricarboxylic acid cycle, processes which are highly relevant in cancer metabolism (30)(31)(32). In our benign versus FTC model, various metabolite intermediates involved in critical metabolic pathways were selected for FTC characterization, including malate, glutamate, and succinate.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have now demonstrated that NOX4 is localized in the mitochondria and produces ROS under pathological conditions (Block et al 2009). An abnormal accumulation of functionally defective mitochondria was reported in oncocytic/Hürthle thyroid carcinomas (Coelho et al 2018). In this context, the decreased enzymatic activity of complexes I and III of the ETC was correlated with high ROS generation by this organelle (Bonora et al 2006).…”
Section: Thyroid Ros-generating Systems: the Nadph Oxidases And The Mmentioning
confidence: 93%
“…Despite its ability to generate ROS during respiratory chain function, the causal relationship between mitochondria as a source of oxidative stress and thyroid tumourigenesis does not seem to be well established (Coelho et al 2018). Mitochondrial ROS are produced by the leakage of electrons from complexes I and III of the electron transport chain (ETC) during oxidative phosphorylation, an important process that generates ATP.…”
Section: Thyroid Ros-generating Systems: the Nadph Oxidases And The Mmentioning
confidence: 99%
“…The majority of metabolism-related molecules, such as GLUT1 (glucose transporter 1), HK1 (hexokinase 1), LDH-A (lactate dehydrogenase A), GLS1 (glutaminase), and MCT1 (monocarboxylate transporter 1) are upregulated in different subtypes of thyroid carcinoma [144]. Inhibitors of glutamine uptake (phenylacetate), glucose metabolism (2-deoxyglucose, 3-bromopyruvate, dichloroacetate), and activators of adenosine monophosphate-activated protein kinase (AMPK; metformin and 5-aminoimidazole-4-carboxamide-ribonucleoside) have all been proposed to regulate metabolic alterations in TC [145].…”
Section: Other Putative Noasmentioning
confidence: 99%